The cult of the dead in central Greece during the Mycenaean period - Gallou, Chrysanthi (2003)
The aim of this thesis is to examine the evidence for the performance of a cult of the dead in LH III Greece with emphasis placed mainly on the material evidence from the typical Mycenaean tombs in the central areas of the Mycenaean dominion, viz. the Argolid, Korinthia, Attica, Boeotia and Euboea during the acme of Mycenaean civilization, that is the LH IIIA-B period.